Effect of a dietary education intervention on biochemical markers in hemodialysis patients with chronic kidney disease: a study in Udupi and Mangalore regions of Karnataka, India: Nutrition Education for haemodialysis patients - Jarupala, Gangadhar Naik; Dharmagadda, Sreedhar; Siddharam , Virendra Ligade; Nagaraju, Shankar Prasad; Guddattu, Vasudeva; Kulkarni, Manjunath; Hebbar, Suvarna (Progress in Nutrition, 2023)
Abstract. Background and aim: Nutritional health is one of the most critical aspects of overall health for chronic kidney disease (CKD) sufferers, particularly those on hemodialysis. In CKD, advanced kidney disease and renal replacement treatment cause protein-energy wasting, leading to various metabolic and nutritional abnormalities. Despite the importance of diet for hemodialysis patients, investigations have revealed that many individuals need more knowledge about optimal nutrition. As a result, inadequate nutrition reduces life quality and increases hemodialysis complications and mortality in these patients. This study aimed to evaluate the impact of a dietary education intervention on biochemical markers in hemodialysis patients with CKD in the Udupi and Mangalore regions of Karnataka, India. Materials and Methods: This is a multicentric and randomised control trial was conducted among 250 hemodialysis patients with CKD at KMC Hospital, Manipal, Dr TMA Pai Hospital Udupi, and Father Muller Medical College Hospital (FMMCH) Mangalore from April 5, 2022, to April 5, 2023. The participants were randomly assigned to either the intervention or control groups. The intervention group received a comprehensive dietary education program, including personalised dietary plans, nutritional counselling, and monitoring, while the control group received standard care without any specific nutritional intervention. The statistical analysis was carried out using the EZR software. Results: The results demonstrated a significant improvement in biochemical markers among participants in the intervention group compared to the control group. Specifically, there was a notable reduction in sodium (p < 0.001), haemoglobin (p < 0.001), and potassium (p = 0.009) levels in the intervention group. Conclusions: The findings of this study highlight the positive impact of a dietary education intervention on improving biochemical markers in hemodialysis patients with CKD.